THE EFFECT OF EXCHANGE RATES, INFLATION AND BI RATES ON PROFITABILITY IN ISLAMIC COMMERCIAL BANKS DURING THE 2016-2022 PERIOD - Hasyim, Fuad; Pratiwi, Ngestiaga; Asmaradhan, Najwa Salsabila; Kurniyadi, Kurniyadi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
A bank is a place to raise distribute and funds public funds. In addition, banks also provide payment services to the public. The main goal of a bank is to obtain profitability. This trial purpose to examine the effect of inflation, exchange rate, and BI rate on profitability (ROA) in Islamic commercial banks for the 2016-2022 period. The residents of this study incoporate all Islamic trade banks for the 2016-2022 period. The type of investigation used in this analysis is quantitative analysis. The data used is secondly data with a causal associative approach. The consequence of this study argue that the independent variables of Exchange Rate, Inflation, and the BI Rate have a significant effect on the dependent variable of Islamic Banking profitability (ROA). And partially, inflation and the BI Rate have a positive effect on ROA at the level α = 10%, while the exchange rate has a negative effect on ROA.